Subscapularis Tendon Repair Using Suture Bridge Technique - Park, Yong Bok (Arthrosc Tech, 2015)
The subscapularis tendon plays an essential role in shoulder function. Although subscapularis tendon tears are less common than other rotator cuff tears, tears of the subscapularis tendon have increasingly been recognized with the advent of magnetic resonance imaging and arthroscopy. A suture bridge technique for the treatment of posterosuperior rotator cuff tears has provided the opportunity to improve the pressurized contact area and mean footprint pressure. However, suture bridge fixation of subscapularis tendon tears appears to be technically challenging. We describe an arthroscopic surgical technique for suture bridge repair of subscapularis tendon tears that obtains ideal cuff integrity and footprint restoration. Surgery using such a suture bridge technique is indicated for large tears, such as tears involving the entire first facet or more, tears with a disrupted lateral sling, and combined medium to large supraspinatus/infraspinatus tears.